2013
DOI: 10.1194/jlr.d029207
|View full text |Cite
|
Sign up to set email alerts
|

A new, long-wavelength borondipyrromethene sphingosine for studying sphingolipid dynamics in live cells

Abstract: apoptosis, and other critical cellular processes during normal cell function and disease ( 1-4 ). Insight into sphingolipid biosynthesis, transport, and subcellular distribution has been acquired by observing fl uorescent sphingolipid analogs within living cells ( 5 ). Sphingolipid derivatives that contain a fl uorophore-labeled N -acyl fatty acid are often used to investigate dynamic processes that involve acylated sphingolipids ( 5 ). Fatty acids that contain a polyene fl uorophore are especially attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(49 reference statements)
5
16
0
Order By: Relevance
“…We have shown that SGPL1 disruption is easily done in a cell line of choice by CRISPR-associated RNA-guided endonuclease Cas9 in a matter of weeks and propose that this should be easily transferable to other cells lines in which functionalized sphingoid bases are used [ 15 , 19 , 20 ], such as cell lines characterized by altered sphingolipid homeostasis. In summary, SGPL1 knockout cell lines provide the basis to studying protein-sphingolipid interaction in physiological and pathophysiological states of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that SGPL1 disruption is easily done in a cell line of choice by CRISPR-associated RNA-guided endonuclease Cas9 in a matter of weeks and propose that this should be easily transferable to other cells lines in which functionalized sphingoid bases are used [ 15 , 19 , 20 ], such as cell lines characterized by altered sphingolipid homeostasis. In summary, SGPL1 knockout cell lines provide the basis to studying protein-sphingolipid interaction in physiological and pathophysiological states of cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for any other sphingoid base containing a modification (e.g. a fluorescent dye) in its backbone [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These fluorescent sphingolipid analogs are advantageous because they afford more flexibility in terms of fluorophore selection, and they can be employed for live cell imaging. Fluorescent sphingolipid precursors that permit observing the lipid distribution that results from biosynthesis and trafficking have also been developed (Peters et al, 2007; Kim et al, 2013). The main drawback to this approach is that the relatively large and chemically distinct fluorophore may alter the interactions between the labeled sphingolipid and other membrane components, which can change the lipid distribution in the membrane (Devaux et al, 2002; Maier et al, 2002; Shaw et al, 2006).…”
Section: Methods To Image Sphingolipid Distribution In the Plasma Memmentioning
confidence: 99%
“…As such, more researchers are changing to fluorescently labeled small molecules within basic sciences [19,20]. Not only is fluorescently labeled ceramide commercially available, but several of the sphingolipids are being produced with fluorescent tags to facilitate safer and sensitive detection of these lipid molecules to implement in biochemical experiments [21,22,23].…”
Section: Expected Resultsmentioning
confidence: 99%